2002
DOI: 10.1007/s00428-002-0639-4
|View full text |Cite
|
Sign up to set email alerts
|

Stromal expression of CD10 in invasive breast carcinoma: a new predictor of clinical outcome

Abstract: CD10 is a cell surface neutral endopeptidase that is not consistently expressed in the stromal cells of the normal breast. Expression of CD10 is sometimes observed in the stromal cells of invasive ductal carcinoma, but its clinical significance has never been studied. Immunohistochemical examination of CD10 was performed in 123 cases of breast cancer. The median follow-up period of all patients was 8.0 years, and univariate and multivariate analyses were performed to evaluate the prognostic significance of str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
141
0
9

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(168 citation statements)
references
References 21 publications
18
141
0
9
Order By: Relevance
“…This dichotomy of expression was also noted, to some extent, in stromal myofibroblasts, which tended to be more commonly and extensively stained with smooth muscle actin rather than CD10, although positive staining with the latter was noted in several cases in this as well as in other studies. 8,37 In this respect, recent studies have suggested the existence of more than one type of myofibroblasts in breast lesions, which vary in their expression of smooth muscle actin and CD34. 38 It has to be added here, that it would be interesting to compare the staining results of the recently introduced nuclear myoepithelial cell marker p63 39 with the more established cytoplasmic markers for these cells in a future study.…”
Section: Discussionmentioning
confidence: 99%
“…This dichotomy of expression was also noted, to some extent, in stromal myofibroblasts, which tended to be more commonly and extensively stained with smooth muscle actin rather than CD10, although positive staining with the latter was noted in several cases in this as well as in other studies. 8,37 In this respect, recent studies have suggested the existence of more than one type of myofibroblasts in breast lesions, which vary in their expression of smooth muscle actin and CD34. 38 It has to be added here, that it would be interesting to compare the staining results of the recently introduced nuclear myoepithelial cell marker p63 39 with the more established cytoplasmic markers for these cells in a future study.…”
Section: Discussionmentioning
confidence: 99%
“…Later studies revealed that 14-3-3s sequesters the Cdc2/cyclin B1 complex in the cytoplasm, which prevents entry into the mitotic phase, thus causing mitotic catastrophe. 18,19 CD10 is an antigen well known as common acute lymphocytic leukemia antigen (CALLA), and recently, expression of this molecule has been reported in hepatocellular carcinoma, 20 mesonephric tumors, 20 trophoblastic tumors, 20 breast cancers 21 and endometrial stromal tumors. 22 CD44 is a cellular adhesion molecule and a complex pattern of CD44 splice variants are expressed in various cancers (recently reviewed by Ponta et al).…”
mentioning
confidence: 99%
“…The stroma of the developing breast is not positive for CD10. Stromal cells in fibroadenomas have demonstrated CD10 positivity [11], and expression has been observed in the stroma and ECM of breast cancers [10,11]. It is hypothesized CD10 may craft a specialized microenvironment to facilitate cancer cell invasion, and/ or may cross-talk with cancerous cells to speed up the cell cycle and promote cell mobility.…”
Section: Bcl-2mentioning
confidence: 99%
“…CD10 is believed to represent a stronger predictive factor for both tumour recurrence and death than node status, tumour size, histologic grade, or clinical size by accordance of Cox's proportional hazards regression model [11]. CD10 expression is associated with estrogen receptor-negativity, high tumour grade and decreased patient survival [10].…”
Section: Bcl-2mentioning
confidence: 99%